Etiology of heart failure in the emergency department of a tertiary cardiac centre of Nepal - Shareef, Miqdhaadh; KC, Man Bahadur; Raut, Roshan; Hirachan, Anish; KC, Bishal; Agarwal, Amit Kumar; Shah, Ram Kishore; Adhikari, Chandra Mani (Nepalese Heart Journal, 2017)
Background and Aims: Heart failure is a major global health problem, but studies on prevalence of heart disease in Nepal are sparse. The aim of this study is to describe the etiology of heart failure patients in emergency department of Shahid Gangalal National Heart Centre. Methods: This was a single centre, prospective, observational study, conducted in the Emergency Department of National Heart Centre, from 1st May to 30th August 2016. All (n=591) consecutive patients with clinical diagnosis of heart failure were evaluated. Results: The mean age of the patients was 56.48 ±19.44 years, with 45.9% males. 31.3% had atrial fibrillation. The commonest cause of heart failure was rheumatic heart disease (25.1%), followed by dilated cardiomyopathy (22.8%), and coronary artery disease (18.1%). The commonest causes in the age group ≤44 years were rheumatic heart disease (61.9%), and congenital heart disease (11.0%). Commonest causes in the age groups 45 – 64 years and ≥ 65 years were dilated cardiomyopathy (29.0% and 26.4%, respectively) and coronary artery disease (22.3% and 24.3%, respectively). The commonest causes in male was dilated cardiomyopathy (26.9%) and in female it was rheumatic heart disease (31.6%). Conclusion: Rheumatic heart disease, dilated cardiomyopathy and coronary artery disease are the commonest cause of heart failure. Appropriate prevention strategies focused at these causes of heart failure are required to decrease the burden of heart failure in Nepal. Nepalese Heart Journal 2017; Vol 14(2), 1-4